SUATU MODEL PENDIDIKAN DENGAN SISTEM BELAJAR MANDIRI - Chaeruman, Uwes Anisa (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2007)
This case study research was focused to find out what, why and how (1) PGMKSBM was implemented; and (2) the diffusion of PGMKSBM was taken. Data collection techniques used were (1) questionnaires; (2) in-depth interviews; and (3) documents and archives analysis. Scope of the study was limited only to the implementation of PGMKSBM in Banten Province. Research findings show that PGMKSBM is an in-service training program aimed to enhance the teacher’ qualification (D-2 or D3) for teachers who are still active teaching but do not has qualification as required, yet. PGMKSBM has some unique characteristics, i.e. (1) it’s in-service training program, not preservice training program; (2) using independent learning system that integrated with the daily teaching practices; (3) applying collaborative action research approach to synergize between theory and daily teaching practices; (4) using authentic assessment technique (portfolio) beside pencil on paper test as learning assessment tools; and (5) use peers and principals as partner and learning resources. Success of PGMKSBM implementation can be showed by some indicators, i.e. (1) quantity of graduated students; (2) improvement of student’ mastery of teaching; (3) teacher performance improvement in school; and (4) improvement on student’ achievement.